Morphological characteristics of the blackspot seabream (Pagellus bogaraveo) tongue: A structural and immunohistochemical study. (24th November 2021) - Abbate, Francesco; Guerrera, Maria Cristina; Levanti, Maria; Laurà, Rosaria; Aragona, Marialuisa; Mhalhel, Kamel; Montalbano, Giuseppe; Germanà, Antonino
Abstract: The blackspot seabream ( Pagellus bogaraveo, Brünnich, 1768) is an omnivorous, predominantly carnivorous fish. In aquaculture, it is fed with pellets rich in proteins and fat. The morphological and functional aspects of the fish tongue, the feeding modality and the tasting capacity are strictly related. Therefore, the aim of this study was to describe by scanning electron, light and confocal laser microscopy, the morphological characteristics of the tongue in this species. It showed an apex, a body and a root. There were rows of teeth on the edges of the mouth and taste pores on all the tongue dorsal surface with folds and furrows. In addition, body and root showed several fungiform‐like papillae in the mucosa of the folds, covered by a weakly keratinized stratified squamous epithelium, can be observed. The papillae were innervated by S100 positive fibres. In the apex, a mesenchymal tissue with vimentin positive star‐shaped stem cells was evident. The results could give a support for a wider use of the blackspot seabream as a farmed species, considering the morphological data as correlated with the potentiality of food discrimination. This provides a basis for possible applications in feeding strategies. The presence, localization and characteristics of the mesenchymal stem cells, as seen also in previous studies, could represent a further basis for future applications in clinical trials.